2020
DOI: 10.1186/s13756-020-0697-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial use and resistance in food-producing animals and the environment: an African perspective

Abstract: Background: The overuse of antimicrobials in food animals and the subsequent contamination of the environment have been associated with development and spread of antimicrobial resistance. This review presents information on antimicrobial use, resistance and status of surveillance systems in food animals and the environment in Africa. Methods: Information was searched through PubMed, Google Scholar, Web of Science, and African Journal Online databases. Full-length original research and review articles on antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
111
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 66 publications
15
111
0
1
Order By: Relevance
“…The most widely consumed antibiotic in animals is oxytetracycline, followed by norfloxacin, enrofloxacin, erythromycin, sulphonamides and co-trimoxazole [124]. Nevertheless, data related to the extent and patterns of antibiotic uses in food-producing animals especially in LMICs are limited [125]. In these countries, antibiotics are being used by farmers without veterinary supervision because of their low cost and availability over-the-counter [98].…”
Section: Antibiotic Uses In Animal Health and The Agricultural Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…The most widely consumed antibiotic in animals is oxytetracycline, followed by norfloxacin, enrofloxacin, erythromycin, sulphonamides and co-trimoxazole [124]. Nevertheless, data related to the extent and patterns of antibiotic uses in food-producing animals especially in LMICs are limited [125]. In these countries, antibiotics are being used by farmers without veterinary supervision because of their low cost and availability over-the-counter [98].…”
Section: Antibiotic Uses In Animal Health and The Agricultural Sectormentioning
confidence: 99%
“…Surveillance data may serve on local, national and international level to improve public health, inform health policies, develop evidence-based policies, trigger responses to health emergencies, provide early warnings of emerging threats and identify long-term resistance trends [77]. AMR surveillance in humans has received more focused attention compared with AMR in animals despite the compiling evidence that the spread resistance has a zoonotic origin [125]. Currently the only country that has publicly available surveillance data on AMR in animals is Colombia [125].…”
Section: Surveillance Of Amr In Humans and Animalsmentioning
confidence: 99%
“…Antimicrobials are widely used in animals to treat infections, prevent diseases and promote growth [ 3 ]. An estimated 131,109 tons of all antimicrobials were used in food animals in 2013 and the figure is projected to rise to 200,235 tons by 2030 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A considerable variation on consumption between countries is reported; ranging from 8 mg/population correction unit (PCU) in Norway to alarmingly high (318 mg/PCU) in China [ 4 ]. Although, the use of antimicrobials is imperative in treating animals, most of its use is directed to prevent infections and promote growth [ 3 , 5 , 6 ]. In the United States, around 70% antimicrobials, which are used to treat human infections are sold for use in food animals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies also found that pathogen E.coli is increasingly becoming multidrug-resistant in Kenya, Nigeria, South Africa, Zimbabwe, and Tunisia. 164 Furthermore, excessive consumption of processed livestock products, particularly processed red meat, is considered a major dietary risk factor that contributes to overweight and the incidence of noncommunicable diseases (NCDs) including cardiovascular disease, cancer, and diabetes, as well as mortality. There has been a significant increase in the prevalence of NCDs over the past two decades in Africa, and the number of deaths linked to NCDs rose by 68 percent between 1990 and 2013.…”
Section: Health Risks For Consumers and Producersmentioning
confidence: 99%